Simulation and modeling for mixed traffic flow with autonomous connected vehicles and human drivers on urban roads - Zhang, Jialu (Nanyang Technological University, 2023)
This thesis focused on the issue of lane change behavior and prediction, which is directly related to the safety of intelligent driving and intelligent vehicles in smart cities. By analyzing actual data, the study investigated the characteristics of lane-changing behavior and developed a model to forecast lane changes. The research compared a number of lane change prediction methods based on different algorithms and confirmed the effectiveness of SVM and MLP methods. It also highlighted the importance of understanding the different types of lane-changing behavior and the factors that influence it, including the lane’s position in relation to highway entrances and exits.